Finely tunable morphology controlled synthesis of spinel-cobalt oxide nanostructures and their electrocatalytic applications. (March 2019) - Kannan, P.; Boopathi, S.; Kumaran, R.; Kundu, M.; Sasidhran, M.; Maduraiveeran, G.
Graphical abstract: Highlights: Synthesis of rice-, dumbbell sheet-, nanoboxes-, and nanosheets spheres- like Co3 O4 nanostructures. Co3 O4 nanosheets spheres display a significantly enhanced electrocatalytic activity. Co3 O4 nanosheets spheres display a low R p value, and high durability. All the Co3 O4 nanostructured materials shows an excellent stability and reproducibility. Abstract: Herein, we synthesize four morphologies of spinel-Co3 O4 nanostructures, including rice-, dumbbell sheet-, nanoboxes-, and nanosheets spheres using a hydrothermal strategy. The surface morphology and size of the Co3 O4 nanostructures are characterized by field emission scanning electron microscopy (FE-SEM), high-resolution transmission electron microscopy (HRTEM), X-ray diffraction(XRD), and electrochemical methods. Among the other Co3 O4 nanostructures, nanosheets spheres- like morphology display a significantly enhanced electrochemical oxidation of sulfite (SO3 2− ) in terms of higher anodic current density (1.50 mA cm −2 ) and low onset oxidation potential (∼1.10 V vs RHE). The Co3 O4 nanosheets spheres offer a large surface area, and numerous active sites for accessing numerous sulfite molecules for efficient and enhanced electrocatalytic responses. Further, the Co3 O4 nanosheets spheres based electrode display a low R p value, and high durability when compared to other nanostructured electrodes. Thus, the Co3O4 nanostructured materials are versatile candidates, and offer a new optimism for use in various electrochemical technological applications.